State-of-the-art Absorption Refrigeration and Heat Pump Cycles - Chen Guangming; Shi Yuqi (Zhileng xuebao)
As the first artificial refrigeration method developed, absorption refrigeration has been around for more than 200 years. In truth, it has been used in civil and industrial applications for more than 60 years. Absorption refrigeration has developed rapidly in terms of theory and application over the past 20 years, and in the refrigerator market occupies a considerable share, has drawn significant attention from both domestic and foreign manufacturers. With an increase in human energy consumption, in-depth research on new and distributed energy sources and their efficient utilization needs to be carried out. The use of waste heat, renewable solar energy, and geothermal energy make heat-driven refrigeration (heat pumps) an increasingly attractive option.Unlike electric-driven vapor compression refrigeration (heat pump) systems, absorption refrigeration (heat pump) technology can be driven directly using thermal energy from low-grade heat sources, operating at a much lower cost than the electric-driven system. Owing to their environmentally friendly features, including safety, noise-free operation, high reliability, and other significant advantages, absorption systems have adopted a water-lithium bromide solution, an ammonia-ammonia solution, or other natural refrigerant as the working fluid. However, absorption systems have a large footprint, a large initial investment, high cooling load, low energy efficiency (direct combustion form), and other deficiencies. In view of these characteristics, the main research directions at this stage include an optimization of the cycle design, the selection of a working fluid, enhancement of the heat and mass transfer of the system components, and optimization of the system control strategy.The absorption cycle, in a narrow sense, refers to a closed, vapor refrigerant absorbed by the solution refrigeration (heat pumps) cycle. This family of cycle, in accordance with its classification of cycle configuration, includes single absorption cycles, multi-absorption cycles, and combined cycles. Single absorption cycles consist of a basic single-effect absorption cycle, diffusion absorption cycles, membrane absorption cycles, heat booster cycles, gravity-driven valve-operation cycles, and self-cascade cycles. A multiple absorption cycle mainly includes a reabsorption cycle, multi-effect cycles, intermediate-effect cycles, multi-stage cycles, intermediate-stage cycles, and GAX cycles. Combined cycles mainly consist of ejection-absorption cycles, compression-absorption cycles, and expansion-absorption cycles.Existing research into absorption refrigeration technologies includes, but is not limited to, solar energy, medium and low temperature level waste heat utilization, combined heat and power, energy storage (cooling and heat storage), membrane exchange materials, high-temperature corrosion-resistant materials, plastic heat exchangers and so on. The existing absorption cycle was designed to satisfy a certain temperature and concentration range. In the face of new applications, new materials and a new absorption of working fluids, novel absorption cycles can be proposed with greater efficiency, wider ranges of heat-source driven temperature and solution concentration.